Transformasi Beut Gampong: Dari Sarana Komunikasi Menuju Gerakan Derma - Arifin, Awaludin (Aceh Anthropological Journal, 2024)
The significance of why the Beut Gampong tradition still persists in the village of Paloh Lada lies in its multifaceted benefits. Specifically, Beut Gampong aims to impart religious knowledge to the community. Therefore, its activities are inseparable from religious rituals (Islam) such as Quranic recitation, studying classical Islamic texts (kitab kuning), reciting blessings upon the Prophet Muhammad (salawat), listening to lectures, and communal prayers. Additionally, Beut Gampong serves as a complex communication tool. Within it, residents discuss various topics to be used as discussion material that will be analyzed by the Tengku (spiritual leader). As a communication tool, Beut Gampong is closely related to instruments that connect the communicator (Tengku) with the congregation. Beut Gampong can be interpreted as a tradition of seeking religious knowledge initiated by both village residents and village institutions themselves. For residents who organize it, these religious gatherings are usually held in private halls, residents' homes, or in locations donated by individuals for public use. Meanwhile, gatherings organized by the village are typically held in the Meunasah or village hall. Moreover, this tradition still endures amidst the challenges posed by the increasingly massive use of communication media for acquiring religious knowledge. However, the role of communication media cannot entirely replace this tradition, considering the values embedded in the traditional communication mechanisms of the Beut tradition are irreplaceable. Among these values are those inherent in the Teungku (teacher), who influences the thoughts and decisions of the community.Abstrak: Salah satu asalan penting mengapa tradisi Beut Gampong masih bertahan di Desa Paloh Lada adalah kemanfaatannya yang tidak tunggal. Secara khusus, Beut Gampong bertujuan untuk membakali pengetahuan agama kepada masyarakat. Karenanya, kegiatan tersebut tidak terlepas dari ritual keagamaan (Islam) seperti membaca Al-Quran, mengkaji kitab Islam klasik (kitab kuning), shalawat, mendengar ceramah, dan bershalawat. Selain itu, Beut Gampong sebagai satu sarana komunikasi yang kompleks. di dalamnya, warga akan membicarakan banyak hal untuk dijadikan sebagai bahan diskusi yang akan dibedah oleh Tengku yang membimbing kegiatan. Sebagai sarana komunikasi, Beut Gampong sangat erat kaitannya dengan instrumen yang dapat menghubungkan antara komunikator (Tengku) dengan jamaah.  Beut Gampong dapat dimaknai sebagai trdisi menuntut ilmu agama yang diinisiasi oleh warga desa maupun institusi desa itu sendiri. Bagi warga desa yang menyelenggarakannya biasanya pengajian dilakukan di balai-balai milik pribadi, rumah warga juga di lokasi yang diwakafkan oleh seseorang untuk kepentingan umum. Sedangkan, pengajian yang diselenggarakan oleh desa biasanya diselenggarakan di Meunasah atau balai desa. Selain itu, tradisi ini masih bertahan di tengah tantangan media komunikasi yang semakin massif digunakan untuk mendapatkan pengalaman belajar ilmu agama. Hanya saja peranan media komunikasi tidak seutuhnya mampu menggantikan tradisi ini secara total mengingat nilai-nilai yang dikandung dalam mekanisme komunikasi tradisional pada tradisi beut tidak tergantikan. Diantaranya ialah nilai-nilai yang terkandung pada diri Teungku (pengajar) yang mempengaruhi pemikiran dan keputusan masyarakat.